2011
DOI: 10.5604/17322693.966833
|View full text |Cite
|
Sign up to set email alerts
|

Activity of N-acetyl-β-hexosaminidase and its isoenzymes A and B in cancer

Abstract: There were approximately 93,060 deaths from cancers in Poland in 2008, and about 105,000 are predicted for the year 2025. Early detection of cancer is a major problem throughout the world, which is why many researchers are still looking for specific and sensitive markers of malignant tumors. Our work is a review of recent publications on activity of N-acetyl-β-D-hexosaminidase (HEX) and its isoenzymes A (HEX A) and B (HEX B) as potential markers of malignant tumors. HEX is the most active of the lysosomal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is evident in cancer metastasis that the level of serum β-hexosaminidase correlates with the likeliness of liver metastasis in variety of cancers, including colon, breast, stomach, pancreas, small bowel, kidney, testis, melanoma, lymphoma, and myeloma ( 108 ). Increased levels of tissue β-hexosaminidase were also reported for breast, kidney, pancreas, thyroid, colon, ovary, brain, salivary gland, stomach, and larynx cancers ( 109 112 ). Thus, it is conceivable by analogy that amebic glycosidases are involved in tissue invasion and extraintestinal dissemination.…”
Section: Strategies For Immune Evasion Of E Histolyticamentioning
confidence: 81%
“…It is evident in cancer metastasis that the level of serum β-hexosaminidase correlates with the likeliness of liver metastasis in variety of cancers, including colon, breast, stomach, pancreas, small bowel, kidney, testis, melanoma, lymphoma, and myeloma ( 108 ). Increased levels of tissue β-hexosaminidase were also reported for breast, kidney, pancreas, thyroid, colon, ovary, brain, salivary gland, stomach, and larynx cancers ( 109 112 ). Thus, it is conceivable by analogy that amebic glycosidases are involved in tissue invasion and extraintestinal dissemination.…”
Section: Strategies For Immune Evasion Of E Histolyticamentioning
confidence: 81%
“…Their activity is also high in other cancers, such as thyroid, renal, pancreatic, ovarian, as well as such diseases as idiopathic arthritis hypertension, glomerulonephritis or following liver transplantation. [43][44][45][46] Ornithine decarboxylase (ODC) activity is higher in colorectal cancer and increases gradually from normal, through adenomatous, to cancerous. It has been shown that ODC activity in microscopically normal colon tissue from patients with CRC is higher than in the normal colon of patients without CRC.…”
Section: Hematopoietic Growth Factorsmentioning
confidence: 99%
“…The presence of HEX was found in the kidneys, spleen, liver [ 17 , 18 ], gastric mucosa, the mucous membrane of the intestine, cerebral cortex, skin fibroblasts, placenta, and lungs [ 19 , 20 ], in cancerous tissues, including in cancer tissues of the liver, pancreas [ 21 ], and a large intestine [ 22 ]. HEX was also determined in body fluids: serum, urine [ 23 , 24 , 25 ], in cerebrospinal fluid, in synovial fluid [ 26 , 27 , 28 , 29 ], in the saliva [ 30 ], as well as in many other tissues and human organs [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%